Upaya Digitalisasi Marketing Dalam Meningkatkan Penjualan UMKM di Kecamatan Juwana - Fanreza Budi Sevina; Azfa Mutiara Ahmad Pabulo (FKIP, Universitas Palangka Raya, 2023)
Utilizing digital marketing has an important role in increasing sales and income so that you can access a wider market reach. Lack of ability, skills and understanding of digital technology is an obstacle for MSME players. To overcome the problems faced by MSMEs in marketing products digitally, education will be provided on how to utilize digital marketing media in selling the products they sell. This service activity aims to provide direction and ways to use digital marketing, especially on the WA Business and Instagram applications, as well as increasing the ability of MSME players to utilize digital as a promotional medium. The method used in this service activity is direct assistance and training for MSME actors with the stages of observation, interviews, activity planning, activity process, end of activity, and documentation. Based on the results of this service activity, MSMEs have begun to know and understand how to use the WA Business and Instagram applications as online sales promotion media.